What does understanding mathematics mean for teachers? : relationship as a metaphor for knowing - Handa, Yuichi (New York : Routledge, 2011)
This book opens up alternative ways of thinking and talking about ways in which a person can "know" a subject (in this case, mathematics), leading to a reconsideration of what it may mean to be a teacher of that subject.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching -- United States; Mathematics -- Study and teaching